1985
DOI: 10.1093/nar/13.9.3357
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of transcription of rDNA: glucocorticoid effects upon initiation and elongationin vitro

Abstract: Various parameters of transcription of cloned mouse rDNA have been examined using extracts from control P1798 cells and from cells treated 24 h with 0.1 microM dexamethasone. Highly purified RNA polymerase I from either source catalyzes nucleotidyl transfer (elongation) at a rate of approximately 30 nucleotides/sec. Extracts from hormone-treated cells are capable of forming stable, preinitiation complexes. The rates of stable complex formation are the same in extracts from control and hormone-treated cells. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 18 publications
2
30
0
Order By: Relevance
“…In the presence of 10-7 M dexamethasone, the proliferation of these cells is reversibly inhibited and the * Corresponding author. rate of 18S and 28S rRNA synthesis is markedly reduced, apparently because of an induced deficiency of a transcriptional initiation factor that is required for polymerase I activity (6)(7)(8). We observed that the synthesis and turnover of rp mRNAs are not significantly affected by the hormone treatment but that the translation of most of these mRNAs, as judged by their polysomal association, is selectively inhibited in a reversible manner.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…In the presence of 10-7 M dexamethasone, the proliferation of these cells is reversibly inhibited and the * Corresponding author. rate of 18S and 28S rRNA synthesis is markedly reduced, apparently because of an induced deficiency of a transcriptional initiation factor that is required for polymerase I activity (6)(7)(8). We observed that the synthesis and turnover of rp mRNAs are not significantly affected by the hormone treatment but that the translation of most of these mRNAs, as judged by their polysomal association, is selectively inhibited in a reversible manner.…”
mentioning
confidence: 74%
“…Coordination at the translation level could be due to a common structural feature or (9,21,27,28,56). In glucocorticoid-treated P1798 cells, the coordination of rRNA transcription and rp mRNA translation may be due to concomitantly induced deficiencies in a polymerase I transcriptional initiation factor (8) and a factor that is normally rate limiting for initiation of rp mRNA translation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific transcription of rDNA requires a component that has been called factor D (43,60), TFID (9), TIF-IB (52), SLi (34,56), or Rib-1 (40) and consists of the TATAbinding protein plus three polymerase I-specific associated factors (13). A second rDNA transcription factor, UBF, binds DNA through multiple regions with homology to high-mobility-group (HMG) proteins, and its observed roles range from being essential for in vitro rDNA transcription (40,53) to being stimulatory (3,35,56) to having no effect on transcription (56), depending on the assay conditions and possibly also on the species examined.…”
mentioning
confidence: 99%
“…The second polymerase I transcription unit is thought to influence enhancer function (Reeder, 1989). RNA polymerase I transcription is regulated by at least three polypeptide trans-acting factors: UBF and a member of the SLI class which probably act as components of a step where polymerase recognises a stable complex and initiates transcription, and an initiation factor that associates tightly with the polymerase but which can be separated from it (Cavanaugh & Thompson, 1985). Termination of polymerase I transcription requires specific interaction between the polymerase and a terminator protein (Kuhn et al, 1990).…”
Section: Physiology and Theoretical Basismentioning
confidence: 99%